Faith, Politics and Eschatology in the Thought of Joseph Ratzinger - Rowland, Tracey (Chrześcijaństwo-Świat-Polityka, 2024)
This paper situates the political theory of Joseph Ratzinger within the tradition of St. Augustine and argues that while his position on the liberal tradition is in some ways ambivalent, he is closer to the British Tory tradition than to the British Whig Tradition. Ratzinger emphasises that Christian faith destroyed the myth of the divine state and replaced it with a conception of the state governed by ‘the objectivity of reason’ and for Ratzinger ‘true human reason involves morality, which lives on God’s commandments’. Ratzinger strongly opposed the alignment of politics with eschatology.